Significance of bile culture surveillance for postoperative management of pancreatoduodenectomy - Sugimachi, Keishi; Iguchi, Tomohiro; Mano, Yohei; Morita, Masaru; Mori, Masaki; Toh, Yasushi (World journal of surgical oncology, 2019)
The management of infectious complications is important in pancreatoduodenectomy (PD). We sought to determine the significance of preoperative surveillance bile culture in perioperative management of PD. This study enrolled 69 patients who underwent PD for malignant tumors at a single institute between 2014 and 2017. Surveillance bile culture was performed before or during surgery. Correlations between the incidence of infectious postoperative complications and clinicopathological parameters, including bile cultures, were evaluated. Preoperative positive bile culture was confirmed in 28 of 51 patients (55%). Bile culture was positive in 27 of 30 cases (90%) with preoperative biliary drainage, and 1 of 21 cases (5%) without drainage (p < 0.01). Preoperative isolated microorganisms in bile were consistent with those detected in surgical sites in 11 of 27 cases (41%). Cases with positive multi-drug-resistant bacteria in preoperative bile culture showed significantly higher incisional SSI after PD (p = 0.01). The risk factors for the incidence of organ/space SSI were soft pancreatic texture (p = 0.01) and smoking history (p = 0.02) by multivariate analysis. Preoperative positive bile culture was neither associated with organ/space SSI nor overall postoperative complications. Preoperative surveillance bile culture is useful for the management of wound infection, prediction of causative pathogens for infectious complications, and the selection of perioperative antibiotic prophylaxis.